2021
DOI: 10.5897/jat2021.0477
|View full text |Cite
|
Sign up to set email alerts
|

Influencing factors of accounting practices: a case study of New Zealand

Abstract: Accounting practices in different countries influenced by several factors. This study has identified some factors those have a great impact on accounting practices in different countries. This study also explains the accounting practices in a specific country: New Zealand, which is one of the developed counties in the South Pacific Ocean close to Australia and a member of commonwealth countries. However, this study is a desk-based research that analyses the existing knowledge on factors influencing accounting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Although the first had an adverse impact on credit risk and ROE, theoretical assumptions and other empirical studies concluded that hazardous business practices might be used to maximize commercial bank profits and that this could be because profitable banks had engaged in risky loans. Similarly, Manab et al (2015) and Nabila and Younes (2011) found a positive correlation between credit risk and profitability.…”
Section: Profitability (Roe)mentioning
confidence: 81%
“…Although the first had an adverse impact on credit risk and ROE, theoretical assumptions and other empirical studies concluded that hazardous business practices might be used to maximize commercial bank profits and that this could be because profitable banks had engaged in risky loans. Similarly, Manab et al (2015) and Nabila and Younes (2011) found a positive correlation between credit risk and profitability.…”
Section: Profitability (Roe)mentioning
confidence: 81%